DRAW-A-PIN: Authentication using finger-drawn PIN on touch devices. Issue 66 (May 2017) - Nguyen, Toan Van; Sae-Bae, Napa; Memon, Nasir
Abstract: This paper presents Draw -A-PIN, a user authentication system on a device with a touch interface that supports the use of PINs. In the proposed system, the user is asked to draw her PIN on the touch screen instead of typing it on a keypad. Consequently, Draw -A-PIN could offer better security by utilizing drawing traits or behavioral biometrics as an additional authentication factor beyond just the secrecy of the PIN. In addition, Draw -A-PIN inherently provides acceptability and usability by leveraging user familiarity with PINs. To evaluate the security and usability of the approach, Draw -A-PIN was implemented on Android phones and 3203 legitimate finger-drawn PINs and 4655 forgery samples were collected through an extensive and unsupervised field experiment over 10 consecutive days. Experimental results show that Draw -A-PIN achieves an equal error rate of 4.84% in a scenario where the attacker already knows the PIN by shoulder surfing. Finally, results from a user study based on the System Usability Scale questionnaire confirm that Draw -A-PIN is highly usable.